Saúde mental de escolares adolescentes após a pandemia por COVID-19 em um ambiente com histórico de violência - Pinheiro, Hugo Nilo Alecrim (2024)
The global emergency created by COVID-19 has confirmed that those most affected by the virus are the most vulnerable and marginalized in society ones. The pandemic did not discriminate, but it did have a disproportionately negative impact on the most socially and economically disadvantaged children and adolescents. Thus, this study aims to evaluate the mental health of adolescent school students after the period of social distancing due to the COVID-19 pandemic, in a community with a recent episode of violence and suicide among students and correlate the findings with of the presence and intensity of symptoms of depression and anxiety with sociodemographic and economic conditions, and personal and family experiences to the context of social distancing. For this, the following questionnaires were applied: "Children Depression Inventory" – CDI, "Beck's Depression Inventory" – IDB and "Multidimensional Anxiety Scale for Children" – MASC, in addition to a sociodemographic questionnaire of the research participant and another of the main caregiver. Data collection was conducted in the second semester of 2022, with student adolescents aged between 15 and 19 years. Throughout the research, lectures were held at the participating school, addressing topics relevant to mental health prevention. The analysis of the results was categorized by the presence or absence of depressive and/or anxious symptoms, according to the cutoff point of each instrument (CDI, greater than or equal to 18, BDI, greater than or equal to 10 and MASC, greater than or equal to 56). Slightly less than half of the students had depressive and anxious symptoms, corroborating previous studies that point to an increase in the prevalence of depression and anxiety among adolescents. This study evaluated adolescents in their school communities, with their experiences of inequalities. Thus, the impact of the COVID-19 pandemic has been exacerbated by social and economic disparity.